Efektivitas Kartu Permainan dan Kombinasi Video Animasi -Kartu Permainan dan terhadap Kepatuhan Minum Tablet Tambah Darah - Bastian, Ardi; Widyowati, Agustin; Yuliawati, Riza; Ernawati, Kristin; Mustikawati, Dian (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background: Screening results at the Baron Health Center, Nganjuk Regency showed that the prevalence of anemia in adolescent girls reached 60.89%. Although counseling and provision of iron tablets to increase hemoglobin levels have been carried out, adolescent girls' adherence to iron tablet is still low. Objective: The study aims to see the differences in two educational methods to improve adolescent girls' compliance in consuming iron tablet Method: A total of 201 adolescent girls were divided into 2 different groups. The first group was given education in the form of game cards, while the second group was given combination education cards and animated videos for 2 months each and 2 hours in every session. This study involves teachers as supervisors during intervention. Data was analyzed using the Wilcoxon test to determine the differences before and after treatment. The Mann Whitney test was used to see the difference in effectiveness between the first and second interventions. Results: Both interventions were significantly effective in increasing compliance with taking TTD (p-value each: Conclusion: Interventions of game cards and combinations of game cards and animated videos have the same level of effectiveness in improving iron tablets consumption compliance.